Why People Obey the Law: Experimental Evidence from the Provision of Public Goods - Lars P. Feld; Jean-Robert Tyran (Center for Economic Studies and ifo Institute (CESifo), 2002)
According to economists, severe legal sanctions deter violations of the law. According to legal scholars, people may obey law backed by mild sanctions because of norm-activation. We experimentally investigate the effects of mild and severe legal sanctions in the provision of public goods. The results show that severe sanctions almost perfectly deter free-riding. However, people also obey law backed by mild sanctions if it is accepted in a referendum. We show that voting for mild law induces expectations of cooperation, and that people tend to obey the law if they expect many others to do so.
Keywords: 330; deterrent effect of legal sanctions; expressive law; social norms; public goods; voting.